Masculinity in Algirdas Landsbergis’s Short Stories - Bankauskaitė, Gabija; Stravinskaitė, Raminta (Respectus Philologicus, 2021)
In interwar and post-war societies, men were required to show endurance, courage, and emotional stability, but their traumas, caused by the experience of war and the economic, political, and social realities of the post-war period, are just started to be analysed. Algirdas Jeronimas Landsbergis (1924–2004), a playwright, prose writer, editor, literary and theatre critic of the Lithuanian diaspora, conveys these themes in his work. The images of masculinity revealed in the texts help clarify the general experience of the society hidden ingician and lover are distinguished.the works and understand what kind of masculinity prevailed in society after the world wars changed the lives of women and men. Using K. G. Jung’s theory of analytical psychology, the article analyses A. Landsbergis’ short stories, which literature researchers less studied. Texts are explored as reflections and shapers of society, and in the case of masculinity, it is discussed what is meant by the archetypes of masculinity recorded in the literature. Based on the work of R. L. Moore and D. Gillette and J. C. Campbell, the archetypes of the divine child, the child prodigy, the Oedipus child and the hero and mature masculinity – the king, warrior, magician and lover are distinguished.